2021
DOI: 10.3390/jrfm14040170
|View full text |Cite
|
Sign up to set email alerts
|

Fantastic Beasts: Blockchain Based Banking

Abstract: Blockchain is one of the primary digital technologies utilised in the finance industry with huge future potential. This study conducts a systematic literature review of a final sample of 407 prior literature from an initial set of 1979 records for the sample period of 2013–2020 with regard to blockchain adoption in banking. This review is further supplemented by a machine learning based textual analysis that identifies key themes, trends, divergences and gaps between academic and practitioner led industry lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 253 publications
0
3
0
Order By: Relevance
“…A study [11] shown how machine learning techniques may be utilized to optimize resource distribution in edge computing environments, which will increase overall effectiveness and performance. An innovative approach was presented in [12], combining data mining and machine learning to identify a more precise resource distribution, to assess the reliability of edge nodes for fog computing. Research [13,14] looked at how different machine learning techniques could be used to assess the dependability of fog computing powered by block chains.…”
Section: Machine Learning-driven Resource Optimizationmentioning
confidence: 99%
“…A study [11] shown how machine learning techniques may be utilized to optimize resource distribution in edge computing environments, which will increase overall effectiveness and performance. An innovative approach was presented in [12], combining data mining and machine learning to identify a more precise resource distribution, to assess the reliability of edge nodes for fog computing. Research [13,14] looked at how different machine learning techniques could be used to assess the dependability of fog computing powered by block chains.…”
Section: Machine Learning-driven Resource Optimizationmentioning
confidence: 99%
“…The amount of transition data on blockchain-oriented remittance platforms create AML analysts is to have a comprehensive overview and ensure fraud predictions. To overcome the obstacles, enhancements in KYC transaction speed, security, transparency, scalability, legislation, regulations (Battistini, 2017;Jayasuriya et al, 2021), and cost reduction are required. Filtering the big data on block-chained remittance creates opportunities to have easy remittance management.…”
Section: Related Workmentioning
confidence: 99%
“…Carbó-Valverde et al (2020) are among the few researchers who have studied technology adoption in areas such as cryptocurrencies, payment gateways, smart contracts, digital accounting, and regulatory networking. However, much of the current attention on technology adoption has focused on its ability to fundamentally change the financial services industry (Daluwathumullagamage & Sims, 2021), rather than on the digital dexterity of the industry's workforce.…”
Section: Introductionmentioning
confidence: 99%